Сутність майнової поруки як акцесорного зобов’язання та її відмежування від суміжних правових категорій - Красуцький, Віталій Віталійович; Красуцький, В. В.; Krasutskyi, Vitalii V. (Одеса, 2019)
Стаття присвячена дослідженню проблематики інституту майнової поруки як акцесорного зобов’язання та її питанню її відмежування від інших інститутів та правових категорій. Досліджуються підстави виникнення та припинення, суб’єктний склад правовідносин застави, де заставодавцем є майновий поручитель, з метою розмежування інституту майнової поруки з інститутом поруки, які являють собою два різні види (способи) забезпечення виконання зобов’язань з відмінними характерами. У статті з’ясовуються теоретичні підходи до розуміння сутності майнової поруки, поняття та правової природи акцесорних зобов’язань майнового поручителя.

The article is devoted to the study of the property guarantee institution’s problem as an accessory obligation and to distinguish it from other institutes and legal categories, caused by the evolutionary transition of Ukraine to the new economic system. The grounds for the emergence and termination of the legal relationship of the pledge, where the pledgor is a property guarantor, with the aim of distinguishing the institution of property guarantee with the institution of suretyship, which are two different types (methods) of ensuring the fulfillment of obligations of distinctive character, are explored. The questions and theoretical approaches to understanding the nature of the property surety are clarified in this study. The concept and legal nature of accessory obligations is analyzed in the article. According to the results of the study, the main aspects of the legal status of the property guarantor and normative basis were systematized and summarized. The authors conclude that the property bail can not arise or cease without the main obligation. Therefore, the person who transfers the thing to the pledge, the mortgagor, will always be a debtor, and the person who takes the pledge thing, the mortgagee will always be a creditor. For the same reason, the realization of mortgage law always has a precondition for the failure of the debtor to fulfill his obligation. There is, therefore, sufficient reason to assert that the property nature of the guarantee is of an accessory nature, which allows it to be distinguished from other categories, taking into account the relevant subject structure and the nature of the security relationship. A clear doctrinal understanding of the investigated legal phenomena and processes will allow to develop mortgage relations, to carry out the necessary analysis, study and improvement of the mechanism of legal regulation of these contractual relations. In addition, the focus is on the need to implement an integrated approach to understanding the accountability of obligations arising between the property guarantor and creditors. This research provides a theoretical and methodological basis for the following researches and has practical importance for increasing the effectiveness of the mechanism for protecting the rights and interests of the parties in obligations of property bail and it improves the legal and regulatory developments in this direction.
Красуцький В. В. Сутність майнової поруки як акцесорного зобов’язання та її відмежування від суміжних правових категорій / В. В. Красуцький // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2019. – Вип. 32. – С. 50-54.
Keywords: застава; майнова порука; майновий поручитель; акцесорне зобов’язання; mortgage; property guarantee; property guarantor; accessory obligation; Research Subject Categories::LAW/JURISPRUDENCE